Fundamentals of Kazakh reference and encyclopedic publications - Uzbekova, Г.; Maikotova, Г.; Alim, Ә.; Zhumatay, А.; Zholdasbay, А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
Unprecedented political and social changes in society require a new assessment of various problems of Social Sciences, studying them from the point of view of a new historical knowledge based on real data and historical materials. But creating a new one is not denying the past. One of the most pressing problems of our time is to learn about the past, learn from history, and step into the future. The purpose of the article is to study the formation and path of the historical development of the Kazakh reference and encyclopedic publication, to determine its place in the history of the country, including in the history of the book. The scientific and practical value of the research work can be attributed to the importance of Kazakh reference books as a means of cognition, education, differentiation of the content of encyclopedic publications in connection with socio-political changes at each stage, indicating the ways of development. There were used methods of historical, philological, statistical, typological, theoretical analysis, description, comparison, evaluation, scientific formulation when studying the topic of the article. The main result of the scientific article is the chronological periodization of the Kazakh reference edition with an indication of the ways of its development. The value of the article lies in determining the journalistic aspect of the encyclopedic case and its own significance and features of encyclopedic articles, etc. The article is intended for researchers of the history of the Kazakh press and reference and encyclopedic literature, students of the Faculty of journalism, and other readers.